Faktor-faktor yang Mempengaruhi Tingkat Pendapatan Rumah Tangga Perajin Kain Tenun di Desa Sade: Factors Affecting Household Income Levels of Woven Fabric Craftsmen in Sade Village - Sukranudin (Aslamiah : Jurnal Pendidikan, Ekonomi, Sosial dan Budaya, 2025)
The main purpose of the company is to create and distribute goods or services needed by consumers to obtain profit or benefits in maintaining the survival of the company and grow and develop in a more advanced direction. The purpose of this study is to determine partially and simultaneously capital, raw materials, labor and transportation have a significant influence on the level of household income of woven cloth craftsmen in Sade village against 36 respondents as research samples. The sampling technique used was interview, observation and questionnaire. The variables proposed are capital, raw materials, labor and transportation. The results of this study indicate that partially the capital variable has a significant influence of 0.000% on the level of household income of woven cloth craftsmen in Pringgasela village, the raw material variable is significant 0.017% on the level of household income of woven cloth craftsmen in Pringgasela village, the raw material variable, labor variable is significant 0.008% on the level of household income of woven cloth craftsmen in Pringgasela village, the transportation variable is significant 0.030% on the level of household income of woven cloth craftsmen in Pringgasela village. From the variables studied, the most influential variable is the capital variable with a regression coefficient of 0.038. And the variable with the smallest influence is the transportation variable with a t-count level of 0.016 which is smaller than the predetermined significance level (0.05).